2018
DOI: 10.15356/2076-6734-2018-3-333-342
|View full text |Cite
|
Sign up to set email alerts
|

Formation of glacier runoff on the northern slope of Tavan Bogd mountain massif based on stable isotopes data

Abstract: This investigation is based on measurements of stable isotopes concentrations (δD and δ18О) in water, snow and ice samples. Glaciers are composed of ice, snow, and fi n of atmospheric origin. The isotopic composition of these components is different, so when melting they form the melted glacial water with different isotope characteristics. Summer precipitation contains the heaviest isotopes, but only a small part of them remains on the glacier. The average isotopic composition of glacier ice represents the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The isotopic composition of the ice from Bolshaya Taldura can be used in further isotopic separation research in the upper Chuya basin as the isotopic composition of meltwater. The obtained mean δ 18 O value is close to the isotopic composition of ice in the Eastern Altai [14]. In the Western Altai, glacier ice must be enriched with stable isotopes according to the greater fraction of summer snow in glacier feeding.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The isotopic composition of the ice from Bolshaya Taldura can be used in further isotopic separation research in the upper Chuya basin as the isotopic composition of meltwater. The obtained mean δ 18 O value is close to the isotopic composition of ice in the Eastern Altai [14]. In the Western Altai, glacier ice must be enriched with stable isotopes according to the greater fraction of summer snow in glacier feeding.…”
Section: Discussionsupporting
confidence: 68%
“…(Seasonal snow was The local meteoric water line (LMWL) was plotted from the event-based precipitation samples for each elevation separately. The slope of these lines is lower than that of the GMWL, which is common for Inner Asia summer precipitation [13,14,26,27]. The LMWL of the samples from the glacier surface (Figure 2, 3000 m) is close to the GMWL.…”
Section: Isotopic Composition Of Ice and Snowmentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, ancient glacial ice plays a significant role in the formation of the water balance of the territory. A similar investigation at the northern slope of Tavan-Bogd mountain massif (the border between Russia, China, and Mongolia) showed that the contribution of melted seasonal snow in glacier runoff at this massif was more significant than at the Tsambagarav [22].…”
Section: Discussionmentioning
confidence: 81%
“…Most of the meltwater samples were taken in the Tavan-Bogd massif. Sampling was carried out in 2015 [19], 2018 and 2021 in the middle of ablation season. Meltwater samples were taken from the edges of most glaciers on the northern slope (Russian part of this massif).…”
Section: Isotopic Composition Of Glacier Meltwatermentioning
confidence: 99%